CONSTITUTIONAL, LEGAL AND EUROPEAN FOUNDATIONS OF STATE REGULATION OF UKRAINE’S ECONOMY - Slipeniuk, Vasyl; Marushchak, Volodymyr; Mykolaichuk, Mykola (Social Development: Economic and Legal Issues, 2026)
The full-scale military aggression against Ukraine has necessitated a reconsideration of the role of the economic system as the material foundation for the state’s vital activities and defense capacity. Ensuring national security under martial law requires prompt and balanced state regulation, which simultaneously must align with European integration processes and commitments regarding the harmonization of domestic legislation with the legal system of the European Union. The purpose of the article is a comprehensive study of the constitutional and European foundations of regulating the economy of Ukraine, as well as the substantiation of legal mechanisms for post-war recovery that would simultaneously ensure national security and meet the criteria for EU membership. The authors found that the national model of economic regulation is based on Articles 13, 15, 17, and 42 of the Constitution of Ukraine, which establish a threefold foundation: freedom of enterprise, economic diversity, human-centricity, and the imperative of economic security as a component of state defense. It is established that under martial law, these constitutional principles are transformed through special legal regimes, where direct administrative intervention is balanced by anti-crisis instruments (automation of registration, relocation, the institute of force majeure). At the European level, the doctrine of “social market economy” (Article 3 of the TEU) and the norms of Articles 101-109 of the TFEU, which limit state aid to protect competition, are analyzed. The role of European competition law and national legislation on state aid is substantiated as a key factor in ensuring market transparency and limiting selective administrative intervention. Based on the results of the study, it is proven that the optimal legal model for the economic development of Ukraine in contemporary conditions lies in a rational combination of mobilization and liberal instruments. Direct methods of administrative control and the narrowing of economic freedom are legitimate solely for reasons of national security protection, whereas indirect fiscal and monetary levers must consistently transform into alignment with the regulatory framework of the European Union.